The Terms of Our Surrender Colonialism, Dispossession and the Resistance of the Innu - Cassell, Elizabeth (University of London Press, 2021)
Based on extensive fieldwork and oral history, The Terms of Our Surrender is a powerful critical appraisal of unceded indigenous land ownership in eastern Canada. Set against an ethnographic, historical and legal framework, the book traces the myriad ways the Canadian state has successfully evaded the 1763 Royal Proclamation that guaranteed First Nations people a right to their land and way of life. Focusing on the Innu of Quebec and Labrador, whose land has been taken for resource extraction and development, the book strips back the fiduciary duty to its origins, challenging the inroads which have been made on the nature and extent of indigenous land tenure-arguing for preservation of land ownership and positioning First Nations people as natural land defenders amidst a devastating climate crisis. It offers a voice to the Innu people, detailing the spirituality practices, culture and values that make it impossible for them to willingly cede their land. The text is intended to bridge the gap in knowledge between legal practitioners and those working at the intersections of human rights, social work and public policy. The book offers a potent template for how we can use the law to fight back against the indignities suffered by all indigenous peoples.